Inclusive Education Strategies in Primary Schools: Integrating Songs and Hexa-Pedia in a Multisensory Individualized Education Program (IEP) - Pety Sumardiani; Amanda Meiliawati; Choiriyah Widyasari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze inclusive education strategies in primary schools through the integration of songs and Hexa-Pedia within a multisensory Individualized Education Program (IEP), focusing on enhancing student engagement, conceptual understanding, and the internalization of inclusive values such as tolerance, empathy, and cooperation. The study employed a qualitative approach with a field research design, applying an emic perspective to obtain authentic insights from students and teachers at an Islamic primary school (MI) in Madiun City. The sample was selected purposively, consisting of classroom teachers, IEP instructors, and students participating in inclusive learning. Data were collected through in-depth interviews, direct observations, and documentation, and analyzed using coding, thematic categorization, and thematic analysis to capture patterns, relationships, and the socio-cultural context of learning. The findings indicate that the integration of songs as an auditory medium and Hexa-Pedia as a visual-kinesthetic medium significantly enhances student engagement, motivation, and active participation, allowing each student to learn according to individual abilities without reducing group interaction. These multisensory media also strengthen conceptual understanding, as students can observe, practice, and repeat learning materials progressively, while fostering the internalization of inclusive values through cooperation, empathy, and respect for diversity. Thus, this integrative strategy creates an immersive, enjoyable, adaptive, and collaborative learning experience, while fostering students’ social character and inclusive behavior. It also provides a significant contribution to inclusive education practices in primary schools and serves as a reference for developing innovative individualized learning strategies.